Understanding the visual search strategies of expert and novice coaches in futsal set pieces - Rodrigues, Manuel; Leite, Nuno; Ribeiro, João N.; Sampaio, Jaime; Araújo, Duarte; Travassos, Bruno (Frontiers in Psychology, 2024)
The aim of this study was to describe the fixation location and the time of the longer fixation of expert and novice futsal coaches before the ball in play in futsal set pieces. Ten expert (ages 48 ± 5) and ten novice coaches (ages 40±7) participated in the study and observed thirty-eight video clips were created to mimic the attack and defensive set-pieces moments of the game. Data were collected in a standardized video analysis task using the pupil invisible eye tracker and processed through the pupil cloud platform.A Mann-Withney test was conducted to evaluate differences in gaze duration between game moments (attack and defense set pieces) and groups (expert vs novice). Gaze duration was also compared for gaze location between groups. For further comparisons, the game moments (attack and defense set pieces) as well as the gaze location were summarized in two-dimensional graphics using correspondence analysis. Results revealed higher values of gaze duration for attack and defense set pieces, for the group of experts in comparison with novices. When considering gaze duration, there were higher values for expert coaches compared to novices for the Attacker 3, Defender 3, Barrier 1 st and Barrier 2 nd gaze locations. The correspondence analysis showed different strategies of visual search and consequently gaze locations for attack and defense set pieces. In particular, there was different correspondence for free kicks between the level of expertise and gaze location, while corner and sideline kicks revealed some correspondence between the groups and the gaze location. While in free kicks coaches should be concern particularly about the relationship between attacker and defender 3 and the barrier 1 st and 2 nd line position, in corner and sideline kicks, coaches should be particularly aware about the relationship between attackers and defenders' positions.